Sistem Informasi Penjualan Pada TB Harmonis Menggunakan Metode FAST - R.M. Nasrul Halim (ISB Atma Luhur, 2020)
The development of computerized technology requires many parties to compete in using a computerized system to improve the performance and effectiveness of a company or agency. Likewise with the Harmonis Bookstore (TB) which so far is still using the manual method in its sales system. This can affect performance and company profits. Overcoming this matter, TB Harmonis created a desktop-based computerized sales information system so that it can improve company performance to be fast, accurate and can do data processing on a large scale which can affect profit and can compete with other similar companies. The system development method in this study uses Framework for the Application of System Thinking (FAST) method. FAST is a combination of several systems development methods consisting of 7 phase of development. Modeling the system using UML consisting of use case diagrams, activity diagrams and class diagrams. The results of this study are book sales information systems which can improve the performance, effectiveness and efficiency of Harmonis TB Palembang.